HIV and mobility in the Lake Victoria Basin agricultural sector: A literature review - Drimie, Scott; Weinand, Julia; Gillespie, Stuart; Wagah, Margaret (International Food Policy Research Institute, 2009)
The Lake Victoria region has the highest HIV prevalence in the East African Community, which comprises Kenya, Uganda, Tanzania, Rwanda, and Burundi. This region also has a significant concentration of commercial agricultural plantations, which rely on mobile workers, an extensive system of out-grower schemes, and linkages with neighboring communities and transportation routes. This paper reviews the relationships between the various components of the plantation system and the spread of HIV, which is a complex and dynamic process. There has been relatively little research on these dynamic interactions, and the relevant policies and programs are generally silent on mobility-induced vulnerability to HIV. As such, this review first examines how the conditions and structure of the migration process may increase HIV vulnerability for migrants, thereby illuminating key challenges. Second, the review considers what may be done to address these issues, particularly within the plantation system. A comprehensive response to HIV would require that the plantation companies engage in efforts against HIV/AIDS across its entire time line (that is, ranging from efforts to prevent infection to attempts to mitigate its full impact on both agricultural workers and the business as a whole). Despite the logic of this argument, we do not yet have strong financial evidence proving that companies should invest in a comprehensive strategy. This critical gap should be addressed. For example, pilot programs on select plantations could be used to show the cost-benefits of addressing HIV/AIDS through a well-designed set of interventions aimed at the different target groups.